Social Media for New Product Launch: A Study of Social Media Platforms Across the RACE Planning Framework - Rautela, Sonica (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The world of marketing communication has been transformed completely by the presence of the internet and internet-enabled platforms. Today, the internet and related platform are home to massive amounts of human dialogues. Human interaction has changed drastically because of the presence of a wide variety of web-based platforms and the proliferation of media. Social Media- a Web 2.0 enabled platform has become an integral part of human life. Also, businesses have started actively participating in these platforms as they have found their users spending a substantial amount of time on these platforms. Thus, social media has become a part of digital marketing which involves the use of a wide variety of digital technologies and digital media to connect to the audience. The RACE i.e. the Reach Act Convert Engage digital marketing framework is a popular infographic, introduced to aid marketers to plan and manage the digital marketing related activities in a more organized manner. The present study aims at exploring the usage of social media at the launch or the commercialization phase of new product development. To fulfill this objective the study uses the RACE digital Planning framework. The study also aims at highlighting the most popular alternatives of social media in each category of the RACE Planning framework in the launch phase of NPD.